Peacebuilding in deeply divided societies : toward social cohesion? - Cox, Fletcher D. (Palgrave Macmillan, 2020)
Contents: Introduction -- 1. Peacebuilding: A Social Cohesion Approach -- 2. Guatemala: National Fragmentation, Local Cohesion -- 3. Kenya: Identity and Insecurity in a Modernizing Society -- 4. Lebanon: Confessionalism, Consociationalism, and Social Cohesion -- 5. Myanmar: Religion, Identity, and Conflict in a Democratic Transition -- 6. Nepal: Identity Politics in a Turbulent Transition -- 7. Nigeria: Frustration, Polarization, and Violence -- 8. Sri Lanka: Social Cohesion ... In the Eye of the Beholder -- 9. Peacebuilding for Social Cohesion: Findings and Implications -- Conclusion.